Fast and direct engraving of iridescent lettering on original product surface using laser interference to prevent counterfeiting. (August 2018) - Ha, Byeong-Hak; Ahn, Sanghoon; Bae, Han-Sung; Kang, Hee-Shin; Kim, Jeng-o; Noh, Jiwhan
Highlights: It has been proposed that diffraction fringes of uniform intervals are generated through laser beam using Fresnel Biprism (FB). A laser-machined polished-metal surface using FB has a unique iridescent interference pattern. By laser processing through FB rotation, letters or numbers are directly engraved on metal surface at different angles to robustly prevent counterfeit. This method is able to distinguish anti-counterfeiting from the naked eye without a separate anti-counterfeit meter. Abstract: We propose the engraving of a unique interference pattern on metal with the use of high-energy 1064 nm laser pulses fired through a Fresnel biprism (FB). The grating is patterned with 500 patterns for 5 ns, and the spacing of patterns can be adjusted according to the physical value of FB. By rotating the FB, the interference pattern is machined into metal to produce an encrypted iridescent character. Encrypted letters are engraved via assigning a serial number and corporate logos to a product (on which the metal is affixed) according to the viewing angle of the interference fringe. The resulting iridescently colored letters or numbers are visible according to their viewing direction. By superimposing letters and numbers, it is possible to store complex passwords, and forgery/counterfeiting can be easily detected by merely using the naked eye and an angle meter.